Technology use in physical education: the teachers’ challenges - Noor Azizah Abd Rahman; Nurwina Anuar; Aidah Abdul Karim; Ahmad Rizal Mohd Yusof (Intelektual Pustaka Media Utama, 2026)
Physical education (PE) is tactile, practical, and participative, making it more challenging to integrate technology than other academic subjects. This study intends to analyse the challenges faced by physical teachers while using digital technology in PE. This research included physical education teachers (PETs) from nine secondary schools in Selangor, Malaysia. Qualitative research design was applied in this study and the data was collected via semi-structured interviews and analysed using thematic analysis. The technological pedagogical content knowledge (TPACK) framework is used to analyse PETs technology education practises and issues. Results revealed that there were seven themes emerged for the obstacles: i) lack of infrastructure; ii) lack of financial support; iii) lack of training; iv) time and space management; v) perception and attitude towards PE; vi) student-related constrains; and vii) lack of educational resources. These findings can be useful to support education in the 21st century whereby the teachers should get extensive technology training to improve their digital skills, as well as regular and ongoing technology integration training.